Միջնադարյան հայ բժշկագիտական խմբագրական դպրոցը - Կարապետյան, Դոնարա
The article studies the important phenomenon of revising medical texts practiced in medieval Armenian medicine. Both the parallels with the Greco-Roman and post-Mashtots traditions of revising texts, and the peculiarities of that practice in the medieval period are manifested. The school of revising medical texts had the following stages: 1. Gagik-Hetum’s Medical Book, 10th-12th cc. (Hetum’s revision of Gagik’s Pharmacopoea, the earliest known Armenian medical book written in the 10th c.: а) common features – borrowing of classical methods of revising texts, b) peculiarity – the revised text acquires its own value as a new work. 2. Amirdovlat‘ Amasiats‘i, 15th c.: а) common features – borrowing of classical and post-Mashtots methods of revising texts, b) peculiarity – revising of his own work resulting in the creation of a new work. The Armenian school of revising texts of Sebastia, 16th-18th cc. 3. Yovasap‘ Sebastats‘i: а) common features – on the base of revising various sources he wrote his own medical book, following Amirdovlat‘’s tradition, b) peculiarity – unique coexistence of elements of medicine and literary fiction and rich illumination of the text, which became a specific instrument of interpreting it. 4. Asar Sebastats‘i: а) common features – he revised his Book of the Art of Medicine, following the Amirdovlat‘ian tradition of revising, b) peculiarity – the new recension of his work contains information on unknown medical works of Mkhit‘ar Herats‘i. 5. Buniat‘ Sebastats‘i: а) common features – classical copying and revision of Amirdovlat‘’s medical works, b) peculiarity – identification of the authors of non- Armenian sources, which is an important instrument for source study. The school of revising texts in medieval Armenian medicine deserves further profound study. Статья посвящена редактированию медицинских текстов в средневековой армянской медицинской литературе. Предпосылки формирования армянской средневековой редакторской школы следует искать в античном и послемаштоцевском периоде. В дальнейшем развитии школы можно различить общие приемы и индивидуальные особенности редактирования у разных авторов. 1. «Лечебник Гагика-Хетума», X-XII вв. – это редакция самого раннего известного нам армянского лечебника X века, «Фармакопеи Гагика», произведенная Хетумом. Хетум пользуется античными методами редактирования, но при этом отредактированный труд получает собственную ценность как новая единица текста. 2. Амирдовлат Амасиаци, XV в.: также заимствует античные и послемаштоцевские традиции редактирования, редактирует собственное сочинение, что приводит к созданию нового текста. Себастийская редакторская школа, XVI-XVIII вв.: 3. Овасап Себастаци: следуя традиции Амирдовлата, редактирует разные источники и на их основе создает свой собственный лечебник, в котором богатый изобразительный ряд сам становится своеобразным инструментом толкования текста. 4. Асар Себастаци: следуя амирдовлатовской традиции редактирования своего же лечебника, создал новый авторский лечебник. Новая редакция труда имеет источниковедческую ценность, так как содержит сведения о неизвестных медицинских трудах Мхитара Гераци. 5. Буниат Себастаци: занимался традиционным переписыванием и редактированием медицинских трудов Амирдовлата, но кроме того, определил авторов неармянских источников, что весьма ценно с точки зрения источниковедения. Представляется, что редакторская школа в средневековой армянской медицине требует дальнейшего изучения.
Keywords: Բժշկագիտություն; Միջնադար